Interaction between birth characteristics and CRHR1, MC2R, NR3C1, GLCCI1 variants in the childhood lymphoblastic leukemia risk - de Carvalho, Vitoria Müller; Chung-Filho, Alython Araujo; Braga, Flávio Henrique Paraguassu; Chagas-Neto, Paulo; Soares-Lima, Sheila Coelho; Pombo-de-Oliveira, Maria S. (Frontiers in Oncology, 2024)
Background: The incidence rate of childhood lymphoblastic leukemia (ALL) differs worldwide. It has been proposed that endogenous cortisol, induced by different triggers, would eliminate pre-leukemic clones originated in-utero. Herein, we tested if the interaction between CRHR1rs242941 C>A, MC2Rrs1893219 A>G, NR3C1rs41423247 G>C, and GLCCI1rs37972 C>T (players in glucocorticoids secretion) and birth characteristics would be associated with ALL risk. Methods: Children aged <10 years were enrolled within the EMiLI project (2012-2020). The study had three steps: (1) Observational analysis of birth characteristics (n, 533 cases and 1603 controls); (2) genotyping to identify single-nucleotide variants (n, 756 cases and 442 controls); and (3) case-only to test gene-environment interactions (n, 402 cases). Genetic syndromes were excluded. The controls were healthy children. The distribution of the variables was assessed through Pearson's chi-square test. Logistic regression (LR) tests were run fitted and adjusted for selected covariates to estimate the association risk. Formal interaction analysis was performed. Genotyping was tested by qPCR with TaqMan probes (CRHR1) or by high-resolution melting (MC2R, NR3C1, and GLCCI1). Hardy-Weinberg equilibrium was accessed by the chi-square test. The genotype-risk association was tested in co-dominant, dominant, and recessive models. The gene-environment interaction odds ratio (iOR) was assessed in case-only. Results: Low birthweight, C-section and low maternal schooling were associated with increased risk for ALL, adjOR 2.11, 95% CI, 1.02-4.33; adjOR 1.59 95% CI, 1.16-2.17; and, adjOR 3.78 95% CI 2.47-5.83, respectively, in a multiple logistic regression model. MC2R rs1893219 A>G was negatively associated with ALL (AG: OR=0.68; 95%CI=0.50-0.94 and GG: OR=0.60; 95%CI=0.42-0.85), while for GLCCI1 rs37972 C>T, TT was positively associated with ALL (OR=1.91; 95%CI=1.21-3.00). The combination of genotypes for MC2R (AA) and GLCCI1 (TT) increased ALL risk (OR=2.61; 95%CI=1.16-5.87). In a multiplicative interaction, MC2R rs1893219 A>G was associated with children whose mothers had > 9 years of schooling (iOR=1.99; 95%CI=1.11-1.55). Conclusion: Our study has demonstrated a significant association between MC2R rs1893219 A>G (reduced risk) and GLCCI1 rs37972 C>T variants (increased risk) and childhood ALL susceptibility. Based on this evidence, genes controlling the HPA axis activity may play a role in leukemogenesis, and further investigation is needed to substantiate our findings.